Evaluation of the Role of Nurses in Maternal Health Education Programs on Reducing Obstetric Complications in Resource-Limited Settings - Khatoon, Mushahida; Kanwal, Shamsa; Ashraf, Saima (Biological and Clinical Sciences Research Journal, 2025)
Maternal health education is a crucial strategy for reducing obstetric complications, particularly in resource-limited settings. Nurses play a central role in delivering structured education to enhance maternal knowledge, promote health-seeking behavior, and improve outcomes. Objective: To evaluate the effectiveness of a nurse-led Maternal Health Education Program (MHEP) in improving antenatal care (ANC) attendance, knowledge of obstetric danger signs, and reducing maternal complications in a Pakistani tertiary care hospital. Methods: A prospective, controlled evaluation was conducted from July to December 2024, involving 99 pregnant women (49 with MHEP, 50 controls). Participants in the intervention group received structured one-to-one and follow-up educational sessions based on WHO/UNICEF guidelines, adapted for local literacy and language needs. The primary outcome was a composite of maternal complications (hypertensive disorders, postpartum hemorrhage, maternal sepsis, prolonged/obstructed labor). Secondary outcomes included ANC process indicators, knowledge scores, and neonatal outcomes. Results: The MHEP group demonstrated significantly higher attendance at≥4 ANC visits (73.5% vs 46.0%, p = 0.005), improved iron–folate adherence (69.4% vs 38.0%, p = 0.0017), and greater birth preparedness (65.3% vs 34.0%, p = 0.0018). Mean knowledge scores on obstetric danger signs were markedly higher (14.2 ± 3.1 vs 10.7 ± 3.4, p<0.001). Composite maternal complications were reduced in the MHEP group (24.5% vs 44.0%; RR 0.56, p=0.041; NNT=5.1). A dose–response relationship was observed, indicating fewer complications with greater session attendance (p = 0.023). Multivariable analysis confirmed an independent reduction in the odds of complications associated with MHEP participation (adjusted OR, 0.41; p = 0.045). Conclusion: Nurse-led maternal health education significantly improved ANC utilization, maternal knowledge, and reduced maternal complications in a resource-limited setting. The observed dose–response effect highlights the importance of sustained, repeated educational engagement. Scaling such interventions could be an effective strategy to improve maternal health outcomes in similar contexts.